Financial Innovation and the Mortgate Marget: The Possibilities for Liability Management by Thrifts: Discussion - Eastin, Richard V. (Journal of Finance, 1976)
Richard V. Eastin, Financial Innovation and the Mortgate Marget: The Possibilities for Liability Management by Thrifts: Discussion, The Journal of Finance, Vol. 31, No. 2, Papers and Proceedings of the Thirty-Fourth Annual Meeting of the American Finance Association Dallas, Texas December 28-30, 1975 (May, 1976), pp. 441-443